Колекція родини Gesneriaceae Dumort. у ботанічному саду Дніпропетровського національного університету - Domnitska, I.L. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
Results of study of the species morphological characters and vital forms for 53 species of family Gesneriaceae Dumort. of collection of Botanical Garden of the Dnipropetrovsk National University are presented.